2020
DOI: 10.1186/s12929-020-0619-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human platelet activation and in vivo vascular thrombosis by columbianadin: regulation by integrin αIIbβ3 inside-out but not outside-in signals

Abstract: Background: Columbianadin (CBN) is one of the main coumarin constituents isolated from Angelica pubescens. The pharmacological value of CBN is well demonstrated, especially in the prevention of several cancers and analgesic activity. A striking therapeutic target for arterial thrombosis is inhibition of platelet activation because platelet activation significantly contributes to these diseases. The current study examined the influence of CBN on human platelet activation in vitro and vascular thrombotic formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The principal results of the present work are that (a) the presence of CBN could depress I Na in a concentration-, time-, and state-dependent manner in GH 3 cells, (b) this compound differentially inhibited the peak and late amplitudes of I Na activated by rapid membrane depolarization with effective IC 50 of 14.7 and 2.8 µM, respectively, (c) it shifted the midpoint of I Na inactivation curve along the voltage axis to a negative potential, despite inability to alter the activation curve of the current, (d) it suppressed peak I Na in a tonic and use-dependent manner, (e) subsequent addition of CBN was capable of depressing the Tef-induced increase in the I Na(P) amplitude activated by the upright isosceles-triangular ramp at either upsloping or downsloping limb, and (f) it mildly inhibited the amplitude of I K(DR) , I K(erg) , or I h , and (g) in HL-1 cardiomyocytes, and CBN was effective at depressing I Na as well as at decreasing the τ inact(S) value of the current. The experimental results enable us to reflect that CBN-mediated change in the amplitude and gating kinetics of ionic currents presented herein tends to be upstream of its action either on cytosolic NOD1/Nf-κB activation [ 2 , 5 , 31 ] or on the activity of antioxidant enzymes [ 14 ], and that it could conceivably participate in the adjustments on different functional activities in electrically excitable cells (e.g., GH 3 or HL-1 cells) occurring in vivo.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The principal results of the present work are that (a) the presence of CBN could depress I Na in a concentration-, time-, and state-dependent manner in GH 3 cells, (b) this compound differentially inhibited the peak and late amplitudes of I Na activated by rapid membrane depolarization with effective IC 50 of 14.7 and 2.8 µM, respectively, (c) it shifted the midpoint of I Na inactivation curve along the voltage axis to a negative potential, despite inability to alter the activation curve of the current, (d) it suppressed peak I Na in a tonic and use-dependent manner, (e) subsequent addition of CBN was capable of depressing the Tef-induced increase in the I Na(P) amplitude activated by the upright isosceles-triangular ramp at either upsloping or downsloping limb, and (f) it mildly inhibited the amplitude of I K(DR) , I K(erg) , or I h , and (g) in HL-1 cardiomyocytes, and CBN was effective at depressing I Na as well as at decreasing the τ inact(S) value of the current. The experimental results enable us to reflect that CBN-mediated change in the amplitude and gating kinetics of ionic currents presented herein tends to be upstream of its action either on cytosolic NOD1/Nf-κB activation [ 2 , 5 , 31 ] or on the activity of antioxidant enzymes [ 14 ], and that it could conceivably participate in the adjustments on different functional activities in electrically excitable cells (e.g., GH 3 or HL-1 cells) occurring in vivo.…”
Section: Discussionmentioning
confidence: 93%
“…f. biserrate Shan et Yuan ( Angelicae Pubescentis Radix or “Duho [Dú huó]” in China). This compound is a coumarin-type compound (an angular dihydrofuranocoumarin), which is increasingly recognized to have various biological activities that include analgesic, anti-inflammatory, and antineoplastic effects [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. This compound has been reported to induce changes in cellular proliferation or apoptosis [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method was applied as described previously [52]. In brief, luciferase/luciferin and Fura 2-AM were used to detect ATP release and calcium mobilization, respectively.…”
Section: Atp Release and Calcium Mobilizationmentioning
confidence: 99%
“…Transportation and absorption kinetics studies revealed that CBN easily entered into the blood and circulated mainly in hepatic tissue [ 17 ]. Our recent study also reported the antiplatelet effect of CBN via different molecular mechanisms and suggested that CBN could act as a potential drug to treat thromboembolic disorders [ 18 ]. Although several basic biological and anti-inflammatory properties of CBN have been explored, the underlying mechanisms of the anti-inflammatory and liver protective effects are unclear.…”
Section: Introductionmentioning
confidence: 99%